‘Capping off’ the development of graduate capabilities in the final semester unit for biological science students: review and recommendations - Firn, Jennifer (Journal of University Teaching and Learning Practice, 2015)
Biology is the most rapidly evolving scientific field of the 21st century. Biology graduates must be able to integrate concepts and collaborate outside their discipline to solve the most pressing questions of our time, e.g. world hunger, malnutrition, climate change, infectious disease and biosecurity. University educators are attempting to respond to this need to better prepare undergraduates to face these challenges by undergoing a dramatic shift in teaching practice from teaching-centered to student-centered and from discipline knowledge to graduate capabilities. With this shift came the development of capstone units—a student’s culminating academic experience where authentic learning environments assist students to develop employer-prized capabilities, e.g. metacognition, networking, time management, collaborative skills. The Queensland University of Technology (QUT) launched a new student centered set of science majors in 2012 and in second semester 2015 will offer a capstone in biology for the first time. My main aims with this report are to understand the theoretical basis and logic behind the development of capstone units and to compare and contrast what other Australian institutions are providing. Based on my findings, I recommend six generic elements for capstone units in biological science: 1. Challenging inquiry-based learning tasks that are intentionally ill defined and complicated, and address cutting edge relevant problems. 2. Small group work activities and assessment that encourages positive constructivist learning. 3. Student centered learning where teachers take the role of coaching and mentoring with students also being provided opportunities to network with members of the professional community. 4. Students perform authentic tasks that involve articulating their findings to peers and experts including the experience of having to defend arguments and decisions. 5. Learning opportunities that include career development skills and training. 6. Explicit modeling of self-aware and meaningful learning to encourage deep learning strategies that foster an appreciation for the nature of science. Overall, I found that the characteristics of capstone units should not be focused on transmitting content, nor simply another controlled application of the scientific method; instead the activities and assessment students perform should be complex, relevant, and realistic to encourage students to move beyond being motivated by grades or fear of failure to wanting to understand concepts deeply and solve problems to make a difference within their future professions and communities.